2005
DOI: 10.1542/peds.2004-1590
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Perinatal HIV Acquisition Among African Infants

Abstract: ABSTRACT. Objective. We investigated gender-specific risks of mother-to-child transmission (MTCT) at birth and at 6 to 8 weeks among infants born to HIVinfected African women.Design. Follow-up study of infants enrolled in 2 randomized, phase III, clinical trials to prevent MTCT, conducted in Blantyre, Malawi, in southeast Africa.Methods. Infants were enrolled at birth and monitored postnatally, and their HIV status was assessed at birth and at 6 to 8 weeks (assessment beyond 6 -8 weeks is ongoing). Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 27 publications
8
27
0
Order By: Relevance
“…First, it contains more girls than boys, a characteristic that also applies to the entire sample of adolescents within the Swiss MoCHiV cohort. We do not know to what extent this may be due to a higher chance that girls contract HIV infection through vertical transmission, as suggested in a few publications [15,16]. Another characteristic of this sample is that only one of the 29 subjects lived with two biological parents.…”
Section: Discussionmentioning
confidence: 88%
“…First, it contains more girls than boys, a characteristic that also applies to the entire sample of adolescents within the Swiss MoCHiV cohort. We do not know to what extent this may be due to a higher chance that girls contract HIV infection through vertical transmission, as suggested in a few publications [15,16]. Another characteristic of this sample is that only one of the 29 subjects lived with two biological parents.…”
Section: Discussionmentioning
confidence: 88%
“…For female donors overall, the older age subgroups had significantly higher HTLV-1 seroprevalence compared with younger subgroups in all pair-wise comparisons (p < 0.0001) except between G [16][17][18][19] and G [20][21][22][23][24][25][26][27][28][29] (Table 1). This trend was also observed for male donors, where G [16][17][18][19] and G 20-29 were not significantly different and all other pair-wise comparisons showed significantly higher seroprevalence for older subgroups (p = 0.0087 between G 20-29 and G 30-39 , and p < 0.0001 for all other pair-wise comparisons, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, a study conducted on ∼1800 infants born to HCV-infected mothers demonstrated twice as much vertical transmission to females as males. 23 For HIV, intra-uterine infection is reported to be female dominant, [24][25][26][27][28] whereas post-natal infection is more common for males. 29,30 One might speculate that the gender-specific risk of transmission varies according to the transmission route.…”
Section: Potential Mechanism Of Paradoxical Male Predominance Of Htlvmentioning
confidence: 99%
“…21 However, this ratio is significantly higher in the children with cancer and HIV, at 2.1:1. Considering the published evidence for a 2:1 ratio of vertical transmission of HIV to female fetuses versus males, 22 this imbalance seems even larger. This confirms the overrepresentation of males in childhood cancers with HIV, which was signaled by others too.…”
Section: The Impact Of Hiv On the Risk Of Cancer In Childrenmentioning
confidence: 96%